Netflix's HR policies - Neck, Christopher P., (SAGE Knowledge. Cases., 2017)
The case discusses how Netflix revolutionized its employee practices by simply treating employees like grownups, and holding them accountable for using their freedom wisely. By focusing on results rather than processes, Netflix gives employees the independence to produce rather than stifling them with processes and procedures. Through the overhauling of its HR practices, Netflix has enjoyed tremendous fiscal results as well as a motivated, driven workforce that is unencumbered by the traditional stressors that employees face.